Test of Flat Burr Mill Type Pepper Grinding - Fadhlan Arief; Achwil Putra Munir; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Quality of pepper in the market is depend on post harvest process, so that this stage needs a very the serious attention. As pepper had two types, the process is also different. The test of flat burr mill type pepper grinding was to know the feasebility of the  mill in white pepper procesing. This research was done in Agricultural Central Laboratorium, Agricultural Department, University of North Sumatera, Medan on October 2014. Parameters observed were effective capacity, percentage of losses seed, moisture content, and the ash content. Results of the research showed that the average effective capacity  was 185.72 gr/minute, and  the percentage of losses seed was 2.9%. The equipment was feaseable to process white pepper, the ash content average was 1.4%, and the average  moisture content was 15.9%. Keyword : Flat burr  grinding mill, white pepper.